Method of project multicriteria decision synthesis on the basis of decision success criterion/Projektų daugiakriterinių sprendimų sintezės remiantis priimamo sprendimo sėkmės kriterijumi metodas - Šarka, Vaidotas; Zavadskas, Edmundas Kazimieras; Ustinovičius, Leonas (Journal of Civil Engineering and Management, 2000)
Method of project multicriteria decision synthesis with decision success criterion is used for realisation of construction projects which require a proper analysis of constituent parts in close relationship of components. Scheme of this method is presented in Fig 3. Multicriteria decision project may be divided into several interrelated building processes and smaller projects. On every level of the whole project, the decision of closeness to ideal solution method is made and, on the basis of the obtained results, several alternatives are chosen. On every separate level, a number of alternatives is selected by the method user. It depends on complexity of the project and on requirements of interested parties. At the last decision stage, there is performed a synthesis using the chosen alternatives and relying on their interrelations. During decision process on the intermediate stages, having eliminated irrational alternatives, effective and precise results are achieved. The developed multicriteria decision synthesis method is one of the elements of the newly created group of multicriteria decision methods. Using this method algorithm, software is prepared that entirely manages the whole decision process from database filling to calculation and result processing.Article in Lithuanian.First Published Online: 26 Jul 2012